Comparasion between Oil Immersed and SF6 Gas Power Transformers Ratings - Osama Elsayed Gouda; Mohamed Dessoky Ali; Ali-Hassan Ali-Hassan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
Power transformers present the largest portion of the capital investment in addition the power transformer remains oil immersed which presents a fire hazard that is particularly objectionable in urban and metropolitan environment. After careful studies of various alternatives to conventional transformer technology to produce a gas insulated power transformer with increased mega volt-ampere ratings, gas insulated power transformer has been developed with a use with non flammable SF6 gas. For changing the insulating material from oil to SF6 gas a comparative study between these types of transformers should be made. In this paper two mathematical models are suggested and simulated by computer programs to calculate the temperature of the cooling mediums and transformer windings. The obtained results are in agreement wit the measured values in the field.